The beef trust - Campbell, Will Ward (My University, 1906)
Introduction: It seems almost egotistical to undertake to treat a subject so great as "The Beef Trust". The Courts have wrestled with it, legislators have wrangled over it, volumes have been written about it, the people have clamored , and the battle is still on. Seager says:- "Monoply means unusually in economics such control over the supply of an economic good as enables the monopolist to regulate its price . The regulation is of course never absolute. It must always have regard to the conditions of production and the extent and elasticity of the consumers' demand. Within certain limits, however, if there is a real monopoly , control is effective and may give rise to monopoly profits.” The question of monopolies is as old as time. The history of the world relates a constant struggle between capitalist and laborer. A "trust" is a species of monopoly, and industrial combination or “caplitalistic monoply" which is large enough to be the controlling factor in its particular line of production. Seager gives as a definition of a "Trust":- "An industrial combination , not a legal or natural monopoly, which seeks to throw off the restraints of competition by absorbing, over-awing or crushing its would be competitors." We have many examples of great trusts in the United States, -The Sugar Refining Company, The United States Feather Company The Standard Oil Trust and many others. Most every great industry is receiving the undivided attention of some combination that is striving to get control of it, but probably a greater number of people are injured by the power of the Beef Trust than that of any other monopoly. This is because it controls the price of our food supply.
Citation: Campbell, Will Ward. The beef trust. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Beef Trust; Monopolies; Economics; Law; Theses